2020
DOI: 10.1007/s00127-020-01937-2
|View full text |Cite
|
Sign up to set email alerts
|

Filipino help-seeking for mental health problems and associated barriers and facilitators: a systematic review

Abstract: Purpose This systematic review aims to synthesise the evidence on behavioural and attitudinal patterns as well as barriers and enablers in Filipino formal help-seeking. Methods Using PRISMA framework, 15 studies conducted in 7 countries on Filipino help-seeking were appraised through narrative synthesis. Results Filipinos across the world have general reluctance and unfavourable attitude towards formal help-seeking despite high rates of psychological distress. They prefer seeking help from close family and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
96
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 77 publications
10
96
1
Order By: Relevance
“…Consequently, mental illness has become the third most common disability in the Philippines, wherein six million Filipinos live with depression and anxiety. Because of this, the country has the third highest rate of mental disorders in the Western Pacific (Martinez et al, 2020 ). Also, the Philippine World Health Organization (WHO) Special Initiative for Mental Health conducted in 2020 showed that ≥3.6 million Filipinos suffer from at least one kind of mental, neurological, or substance use disorder (Department of Health, 2020 ).…”
Section: The State Of Mental Health In the Philippinesmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, mental illness has become the third most common disability in the Philippines, wherein six million Filipinos live with depression and anxiety. Because of this, the country has the third highest rate of mental disorders in the Western Pacific (Martinez et al, 2020 ). Also, the Philippine World Health Organization (WHO) Special Initiative for Mental Health conducted in 2020 showed that ≥3.6 million Filipinos suffer from at least one kind of mental, neurological, or substance use disorder (Department of Health, 2020 ).…”
Section: The State Of Mental Health In the Philippinesmentioning
confidence: 99%
“…Suicide rates are reported to be at 3.2 per 100,000 population with higher rates among males (4.3/100,000) than females (2.0/100,000). However, these numbers may be underreported because suicide cases may sometimes be misclassified as “undetermined deaths” (Lally et al, 2019 ; Martinez et al, 2020 ). The WHO estimated that 154 million Filipinos suffer from depression, 1 million from schizophrenia, and 15.3 million from substance use disorders, while 877,000 die due to suicide every year (Department of Health, 2018 ).…”
Section: The State Of Mental Health In the Philippinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, mental illness has become the third most common disability in the Philippines, wherein six million Filipinos live with depression and anxiety. Because of this, the country has the third highest rate of mental disorders in the Western Pacific (Martinez et al, 2020). Also, the Philippine WHO Special Initiative for Mental Health conducted in 2020 showed that ⩾ 3.6 million Filipinos suffer from at least one kind of mental, neurological, or substance use disorder.…”
Section: The State Of Mental Health In the Philippinesmentioning
confidence: 99%